Pengaruh Penerapan Akad Qard Dan Ijarah Terhadap Minat Nasabah Pada Produk Gadai di Bank Syariah Indonesia (BSI) KC Binjai - Abi Waqqosh; Saparuddin Siregar; Sugianto Sugianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study was to find out how the effect of qard and ijarah contracts on customer interest in using pawn products at the Indonesian Islamic Bank (BSI) Kc Binjai. This study used quantitative research in its analysis. The population used in this study is all people who use pawn services at Bank Syariah Indonesia (BSI) Kc Binjai. The data analysis used is data quality analysis, multiple linear regression test, and hypothesis testing. From the results of the study, it is known that the qard and ijarah contracts have a positive and significant effect on customer interest in using pawn products at Bank Syariah Indonesia (BSI) Kc Binjai